T cell immunotherapy for solid tumors: limitations, progress, and future prospects - Wang, Yinuo; Zhang, Boyu; Wang, Yajie; Tan, Yuan; Hu, Xiaoqian; Che, Xuan; Feng, Mei (Frontiers in Immunology, 2026)
T cell-based immunotherapies have achieved notable success in the treatment of hematological malignancies, particularly through the application of chimeric antigen receptor (CAR) T cells. However, the clinical efficacy of such approaches in solid tumors remains limited due to a range of intrinsic and extrinsic barriers, including tumor antigen heterogeneity, the immunosuppressive tumor microenvironment (TME), and insufficient T cell infiltration and persistence. Despite these challenges, significant advances have been made in recent years in the development of CAR-T cells, T cell receptor-engineered T cells (TCR-T), and tumor-infiltrating lymphocytes (TILs) for solid tumors. This review provides a comprehensive overview of the current landscape of T cell immunotherapies targeting solid tumors. We examine the underlying mechanisms and design principles of each therapeutic modality and summarize the clinical progress in a tumor-specific context. Particular attention is given to the biological and technical challenges that impede treatment efficacy, including antigen escape, on-target off-tumor toxicity, and the suppressive features of the TME. Furthermore, we discuss emerging strategies aimed at overcoming these obstacles, such as combinatorial antigen targeting, immune checkpoint blockade, synthetic biology tools, and gene editing technologies. Finally, we outline future perspectives in the field, emphasizing the importance of precision immunotherapy and the integration of multi-omics data to enhance T cell functionality and specificity. This review aims to inform ongoing research and guide the clinical translation of T cell-based therapies for solid tumors.